Trends in abusive and nonabusive injury hospitalizations in young children in Texas, 2004-2018 - Cain, Cary M. (Child maltreatment, 2022)
Hospitalization data provide context to understanding abusive and non-abusive injuries and how these hospitalizations change over time. The purpose of this study was to utilize Texas inpatient hospitalization data to assess age-related differences among infants (<12 months of age) and toddlers (12-59 months of age) in injury trends and patterns of injury among abusive and non-abusive hospitalization encounters over a 15-year time period. For both age groups, pediatric hospitalizations for non-abusive injuries decreased significantly over time; however, hospitalizations for abusive injuries did not. Compared to non-abusive injury hospitalizations, abusive injury hospitalizations were statistically more likely to involve more body regions and were associated with fractures, internal organ injuries, and superficial wounds. Abusive injury hospitalizations had longer lengths of stay and resulted in higher illness severity scores. Toddler injury hospitalizations were associated with most of the body regions, with the exception of traumatic brain injury for which the odds of hospitalization were higher for infants. This study confirms the persistence of abusive injury hospitalizations and the age-related susceptibility to certain injuries comparing infants and toddlers. The findings reflect the clinical documentation and decision making of pediatric practitioners in a large state over 15 years and inform the trends in identification of injuries which are most common and consistent by age and intent.